Assessing the effect of phosphorus application on early growth of maize at Sunderbazar, Lamjung, Nepal (Journal of Maize Research and Development, 2016)
Phosphorus (P) is an essential nutrient element for maize production. A pot experiment was conducted during May-June, 2015 to assess the effects of different rates of P on early growth of maize plant at Sundarbazar, Lamjung. Two maize varieties (Rato Makai and Poshilo Makai-1) were subjected to four P levels (0 kg ha-1,13 kg ha-1, 18 kg ha-1, and 23 kg ha-1) in randomized complete block design with four replications. The effects of different P level on root elongation, root biomass, plant height, root shoot biomass ratio and total dry matter were investigated at 45 days after sowing. For all parameters, the maximum value was obtained when soil was added with 18 kg P ha-1 & the minimum value under the control of 0 kg P ha-1. Maize varieties differed significantly in terms of all the parameters under study, and Poshilo Makai-1 performed better than Rato Makai at all P levels. So, from this result, it can be concluded that Poshilo Makai-1 appeared to be P efficient over Rato Makai at early growth stage. However, it would be necessary to look at the response of crop up to maturity and at wider range of P to have the better insight of their relative performance.